Complimentary use of dating and hydrochemical tools to assess mixing processes involving centenarian groundwater in a geologically complex alpine karst aquifer. - Gil-Márquez, José Manuel; de la Torre, Beatriz; Mudarra-Martínez, Matías; Sültenfuß, Jürgen; Andreo-Navarro, Bartolomé (Wiley, 2020)
Environmental dating tracers (3H, 3He, 4He, CFC-12, CFC-11, SF6) and the natural spring response (hydrochemistry, water temperature, and hydrodynamics) were jointly used to assess mixing processes and to characterize groundwater flow in a small carbonate aquifer with complex geology in southern Spain. Results evidence a marked karst behavior of some temporary outlets, with sharp and rapid responses to precipitation events, while some perennial springs show buffer and delayed variations with respect to recharge periods. The general geochemical evolution shows a pattern, from higher to lower altitudes, in which mineralization and the Mg/Ca ratio rise, evidencing longer water-rock interaction. The groundwater age in the perennial springs —as deduced from CFC-12 and 3H/3He— points to mean residence times of several decades, although the difference between the two methods and the large amount of radiogenic 4He in samples indicates a contribution of old groundwater (free of 3H and CFC-12). Lumped Parameter Models and Shape-Free Models were created based on 3H, tritiogenic 3He, CFC-12, and radiogenic 4He data in order to interpret the age distribution of the samples. Results evidence the existence of two mixing components, with an old fraction ranging between 160 and 220 years in age. The correlation of physicochemical parameters with some dating parameters derived from the mixing models serves to explain the hydrogeochemical processes occurring within the system. Altogether, long residence times are shown to be possible in small alpine systems with a clearly karst behavior if the geological setting features highly tectonized media including units with diverse hydrogeological characteristics. These findings highlight the importance of applying different approaches, including groundwater dating techniques, when studying such groundwater flow regimes.
https://v2.sherpa.ac.uk/id/publication/7459
Keywords: Aguas subterráneas; Karst (Geología); Groundwater dating; Alpine karst; Complex aquifer; Groundwater age distribution; Binary mixing; Hydrochemistry